Beyond the EJ model: Entrepreneurial orientation and industry choice of Ghanaian entrepreneurs - George Acheampong (Journal of Global Entrepreneurship Research, 2017)
This paper seeks to understand an entrepreneur's decision to either the services or manufacturing sectors of the Ghanaian economy. This objective is significant because it provides an extension of current stream of literature, specifically, the Evans and Jovanovic (EJ) Model which focuses largely on an entrepreneur's decision to start a business. The study seeks to understand the industry choice of an entrepreneur by adopting the entrepreneurial orientation concept as its theoretical base. Data for the study is collected from entrepreneurs in Accra, Ghana and analysed by means of structural equation modelling precededwhich is by a confirmatory factor analysis of the entrepreneurial orientation (EO) scale. The estimation results indicate that, entrepreneurs with high risk-taking thresholds are more likely to enter into the manufacturing sector while innovative individuals are more likely to enter into the services sector. Proactiveness is not seen to be significant. The results show that an entrepreneur's personal characteristics influence the choice of industry he or she will participate in.
Keywords: 650; Entrepreneurial orientation; Industry choice; Entrepreneurs; EJ Model; Ghana